Resercoir space characteristics and pore structure of Jurassic Lianggaoshan Formation lacustrine shale reservoir in Sichuan Basin, China: Insights into controlling factors - Lai, Qiang; Qi, Lin; Chen, Shi; Ma, Shaoguang; Zhou, Yuanzhi; Fang, Pingchao; Yu, Rui; Li, Shuang; Huang, Jun; Zheng, Jie (Frontiers in Earth Science, 2023)
The Jurassic Lianggaoshan Formation lacustrine shale oil is the most potential exploration target of unconventional hydrocarbon resource in Southwest China. In this study, nuclear magnetic resonance (NMR), scanning electron microscopy (SEM), low-temperature N2 adsorption (LTNA), and high pressure mercury intrusion (MICP) are intergrated to reveal pore structure and its controlling factors of Lianggaoshan Formation lacustrine shale reservoir. Results indicate that three types of lithology combination are classified in the Jurassic Liangggaoshan lacustrine shale reservoir. Type A comprises pure shale. Type B is characterized by frequent shell limestone interbedding. Type C is characterized by frequent siltstone interbedding. The Type C shale is characterized by relatively high proportion of organic pores, high development and good connectivity of nanopores, and highest PV and SA. The nanopores of Lianggaoshan lacustrine shales are mainly dominated by mesopores and part of the macropores. Among them, the PV and SA are both mainly dominated by micropores. The enrichment of organic matter has little effect on the formation of micropores, and does not influence the mesopore-macropore development. Quartz in Lianggaoshan lacustrine shale does not significantly affect the formation of micropore and mesopore-macropore. Intraparticle pores within calcite particles constitute part of mesopore-macropore but not micropores. Clay minerals has no perceptible effect on the formation of micropore and mesopore-macropore.